Structuring Natural Language to Query Language: A Review - Nethravathi, B.; Amitha, G.; Saruka, A.; Bharath , T. P.; Suyagya, S. (Engineering, Technology & Applied Science Research, 2020)
SQL (Structured Query Language) is a structured language for specialized purposes used to communicate with the data stored in a database management system. It uses dynamic and sophisticated query commands for processing and controlling data in a database, which can become an obstacle for users with no previous experience. In order to address this constraint, we have analyzed the existing models in Natural Language Processing, which convert a native-language query into an SQL query. Thus, any novice user can use the SQL program and eliminate the need to generate any complex queries. This work is a detailed survey of the existing literature.